CONVERTED VILLAIN: A STUDY ON GRU’S CHANGING CHARACTER TRAITS IN DESPICABLE ME - Regina Tabentane; Setefanus Suprajitno (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
This article concerns with Gru’s character development in Despicable Me. In this movie, Gru, the father of three daughters is described as a villain. However, later on Gru becomes a good man. In this article, I am interested in analyzing the reasons or factors why Gru’s character traits change and how his changing character traits effect him and others. In my analysis I examine the process of Gru’s changing character traits by using the theories of characterization and conflict. Beside those theories I also use the theory of personality to get a better understanding of the effect of his character development. The findings show that his three daughters’ love plays a role in changing his character. As a result, Gru becomes a good man and he is well accepted by others. Through Gru’s experiences, I conclude that it is very important that people should show their understanding to others and be mindful to others feeling. In this way, they can have a more meaningful life.